Laboratory infection of three species of fishes with the water mold Saprolegnia parasitica and methods of their treatment - Badr, Sanaa Qasem; Al-Duboon, Abdul-Hafiz; Muhsin, Tawfiq M. (Iraqi Journal of Aquaculture, 2022)
Three fish species (Cyprinus carpio, Ctenopharyngodon idella and Carrassius auratus auratus) were artificially infected with the fungus Saprolegnia parasitica. The infection was done under certain laboratory circumstances represented by a change in temperature (10, 15, 20, 25 and 30°C) and in nutrients (normal, decrease and increase in nutrients) under a constant pH. The statistical analysis of infection results showed that the influence of temperature on fungal infection was dominant. Thus, when temperature decreases, infection increases and vice versa. Time and nutrients were less influential. The infected fish were treated with different remedial materials (sodium chloride, methylene blue, potassium permanganate, ketoconazole and fluconazole). All these materials showed positive results in the total treatment of the infected fishes but the best was the sodium chloride at a concentration of 9%.